Targeted Theranostic Nano Vehicle Endorsed with Self‐Destruction and Immunostimulatory Features to Circumvent Drug Resistance and Wipe‐Out Tumor Reinitiating Cancer Stem Cells. Issue 38 (14th August 2020) - Joseph, Manu M.; Ramya, Adukkadan N.; Vijayan, Vineeth M.; Nair, Jyothi B.; Bastian, Blossom T.; Pillai, Raveendran K.; Therakathinal, Sreelekha T.; Maiti, Kaustabh K.
Abstract: The downsides of conventional cancer monotherapies are profound and enormously consequential, as drug‐resistant cancer cells and cancer stem cells (CSC) are typically not eliminated. Here, a targeted theranostic nano vehicle (TTNV) is designed using manganese‐doped mesoporous silica nanoparticle with an ideal surface area and pore volume for co‐loading an optimized ratio of antineoplastic doxorubicin and a drug efflux inhibitor tariquidar. This strategically framed TTNV is chemically conjugated with folic acid and hyaluronic acid as a dual‐targeting entity to promote folate receptor (FR) mediated cancer cells and CD44 mediated CSC uptake, respectively. Interestingly, surface‐enhanced Raman spectroscopy is exploited to evaluate the molecular changes associated with therapeutic progression. Tumor microenvironment selective biodegradation and immunostimulatory potential of the MSN‐Mn core are safeguarded with a chitosan coating which modulates the premature cargo release and accords biocompatibility. The superior antitumor response in FR‐positive syngeneic and CSC‐rich human xenograft murine models is associated with a tumor‐targeted biodistribution, favorable pharmacokinetics, and an appealing bioelimination pattern of the TTNV with no palpable signs of toxicity. This dual drug‐loaded nano vehicle offers a feasible approach for efficient cancer therapy by on demand cargo release in order to execute complete wipe‐out of tumor reinitiating cancer stem cells. Abstract : Here, the precise elimination of drug‐sensitive and resistant cancer cells along with cancer stem cells with the intelligent fabrication of a targeted theranostic nano vehicle (TTNV) is demonstrated. A tumor‐targeted biodistribution followed by a striking pattern of bioelimination of this TTNV contributes to the wipe‐out of tumor mass on both folate receptor‐positive and CD44‐positive tumor‐bearing mice.